Optimization Of Peanut Bread Production Using The Cutting Plane Method at UD. Hj. Eliya Lubis - Siti Khadijah Laoly; Rina Filia Sari (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
This research aims to optimize the production of peanut bread at UKM Peanut RotiHj. Eliya Lubis in Tebing Tinggi City. The main challenges faced are fluctuating raw material prices and unstable consumer demand, which affect the production process. The research uses the cutting plane method to complete an integer linear program to determine optimal production quantities. This method was chosen because it is effective in solving optimization problems with integer results, which are relevant for in-house production. The research results show that the cutting plane method is able to produce better optimal solutions than other methods, such as branch and bound, thereby increasingproduction efficiency and company profits. . Based on the results of management using the cutting plane method, the profit obtained in December 2023 is IDR. 281.734.404,4 by producing 1.248 peanut butter pineapple breads, 2.175 strawberry jams, 595 cappuccino jams, 6.676 chocolate jams, 2.618 red bean breads and 4.020 green beans. The profit earned in January 2024 is IDR. 276.866.635 by producing 371 peanut butter pineapple breads, 111 strawberry jams, 1.605 cappuccino jams, 1.333 chocolate jams, 4.538 red bean breadsand 2.714 green bean breads. In this case, income in January 2024 decreased drastically due to an increase in raw material prices so that consumer demand was difficult to fulfill.